Trigeminal Neuralgia: Comprehensive Treatment Strategies in a Multidisciplinary Approach – A Literature Review - Pomirska, Agata; Pomirski, Bartosz; Wilewska, Anna; Biernikiewicz, Julia; Alabrudziński, Konstanty; Biernikiewicz, Milena; Borowiec, Agnieszka; Dach, Aleksandra; Borowiec, Kinga; Kwaśniewska, Paulina (Journal of Education, Health and Sport, 2026)
Introduction. Trigeminal neuralgia (TN) is a rare but debilitating craniofacial pain disorder characterized by sudden, severe, electric shock-like episodes affecting one or more branches of the trigeminal nerve. Despite its low prevalence, TN has a profound impact on quality of life. Accurate diagnosis and subtype classification are essential for guiding treatment. Advanced neuroimaging techniques help identify structural causes and guide therapy. Purpose. This review offers a comprehensive, evidence-based summary of current treatment strategies for TN, including pharmacological, surgical, and supportive modalities. Special attention is given to recent advances and options for patients with refractory or complex cases. Materials and Methods. This review is based on a structured analysis of peer-reviewed literature retrieved from PubMed, Google Scholar, and the Cochrane Library. Selection prioritized systematic reviews, randomized controlled trials, clinical guidelines, and high-quality cohort studies published between 2000 and 2024. Emphasis was placed on clinical relevance and methodological rigor. Conclusion. Effective management of trigeminal neuralgia demands an individualized, stepwise approach. While carbamazepine and oxcarbazepine remain first-line treatments, a significant subset of patients requires surgical or adjunctive therapies. Microvascular decompression offers the best long-term outcomes in classical TN, whereas less invasive procedures and botulinum toxin injections may benefit selected patients. Neuromodulation techniques are emerging alternatives for drug-resistant cases. Multidisciplinary care is essential for accurate diagnosis and individualized treatment.